2022
DOI: 10.1080/23144599.2022.2040176
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic pathogens survey in free-living long-tailed macaques in Thailand

Abstract: Long-tailed macaques ( Macaca fascicularis ) are known to harbour a variety of infectious pathogens, including zoonotic species. Long-tailed macaques and humans coexist in Thailand, which creates potential for interspecies pathogen transmission. This study was conducted to assess the presence of B virus, Mycobacterium spp., simian foamy virus (SFV), hepatitis B virus (HBV), and Plasmodium spp. in 649 free-living Thai long-tailed macaques thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 42 publications
0
13
3
Order By: Relevance
“…MTBC shedding in 10/23 common long-tailed macaques populations in our study differed from a report published elsewhere ( 31 ), in which Mycobacterium spp. were not detected in any of 649 free-living common long-tailed macaques from 26 locations ( 31 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…MTBC shedding in 10/23 common long-tailed macaques populations in our study differed from a report published elsewhere ( 31 ), in which Mycobacterium spp. were not detected in any of 649 free-living common long-tailed macaques from 26 locations ( 31 ).…”
Section: Discussioncontrasting
confidence: 99%
“…MTBC shedding in 10/23 common long-tailed macaques populations in our study differed from a report published elsewhere ( 31 ), in which Mycobacterium spp. were not detected in any of 649 free-living common long-tailed macaques from 26 locations ( 31 ). This discrepancy might be because of differences between studies in sampling locations, specimen collection methods, DNA extraction processes, and PCR performance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the previous study, Kurniawati et al [21] reported that increasing of long-tailed monkeys' population would create a situation where every individual gets closer to each other, increasing the risk of disease transmission. Wild animals are the source of zoonotic diseases, and primates are reservoir hosts of several infectious diseases, including Mycobacterium spp., Simian Foamy Virus (SFV), hepatitis B virus (HBV), and Plasmodium spp [22]. Our observation found 8 cases of AG 2 behaviour and 12 cases of AG 3.…”
Section: Resultsmentioning
confidence: 59%
“…that were found in the long-tailed macaques at Kosumpee Forest Park, the possibility exists that these macaques act as natural reservoir hosts for leptospirosis. Given the close contact between the macaques and local resident in this shared environment, the opportunity for cross-transmission of zoonotic pathogens presents a real concern; one that also has been noted by others [ 20 , 21 ]. The occurrence of Leptospira seropositivity from the long-tailed macaques in this study (13.33%) was lower than what has been found in some recent studies from other countries, including Southern, Central, and Eastern Thailand, with 48 out of 223 (21.52%) long-tailed macaques [ 21 ]; 8 out of the 12 monkeys (66.66%) from Sarawak, Malaysia [ 22 ]; 39 out of 83 wild African green monkeys (47%) on the Caribbean island of Saint Kitts, India [ 23 ]; 16 out of 52 capuchin monkeys (30.77%) from Colombia [ 24 ]; and 39 out of 50 tufted capuchin monkeys (78%) from Southeast Sao Paulo state, Brazil [ 25 ].…”
Section: Discussionmentioning
confidence: 98%